Solid Surfaces, Interfaces and Thin Films - Luth, Hans (Berlin : Springer, 2010)
Solid Surfaces, Interfaces and Thin Films has been used meanwhile as a standard textbook around the world at many universities and research institutions. Even though surface and interface physics have become a mature science branch, their theoretical concepts and experimental techniques are of higher importance than ever before because of their impact on nanostructure physics. Surface and interface physics form the basis for modern nanoscience, be it in quantum electronics, in catalysis, in corrosion, or in lubrication research. This explains the ever-growing demand for education in these elds. It was therefore time to carefully revise the book and bring it up to latest dev- opments both in fundamental research and in application. Concerning new ma- rial aspects topics about group III nitride surfaces and high k-oxide/semiconductor heterostructures have been included. Recent developments in these material classes are of essential importance for high-speed/high-power electronics and advanced - based CMOS technology on the nanometer scale. The novel eld of spin electronics or spintronics having been initiated by the detection of the giant magnetoresistance (GMR) by Peter Grunberg and Albert Fert (Nobel Prize 2007) required a more extensive consideration of anisotropy effects in thin magnetic lms. For the devel- ment of purely electrical spin switching devices based on spin effects rather than on semiconductor space charge layers, a prerequisite for high-speed, low-power sp- tronics, the spin-transfer torque mechanism shows some promise. Correspondingly this topic is discussed in direct connection with the GMR in this new edition.
Includes Reference 561-572p.; Index 573-577p.
Keywords: Interface physics; Solid surfaces; Surfaces physics; Thin films; Physics